“Struggling like fish out of water”: a qualitative case study of Chinese international students’ acculturative stress in the UK - Jiang, Xiaoming; Xiao, ZhiMin (Frontiers in Education, 2024)
This research aims to explore the acculturative stressors experienced by Chinese international students in the UK and investigates their perceptions of intercultural mentoring programmes offered at UK universities. To achieve these objectives, the study utilises primarily qualitative data gathered from 12 semi-structured interviews, exploring Chinese international students’ wellbeing and their perceptions about intercultural mentoring programmes. The findings indicate that the wellbeing of Chinese international students was influenced by a range of macro and micro acculturative stressors, including academic integration, language barriers, social integration, and the COVID-19 pandemic. However, the study surprisingly found that perceived cultural differences between China and the UK, as well as homesickness, were not the main sources of stress for Chinese international students. Regarding intercultural mentoring programmes, this research finds that their introduction by UK universities represents a positive effort to enhance intercultural competence and overall wellbeing of international students. Nevertheless, the research has identified four main issues requiring consideration: mentor qualifications, limited mentor availability, effective mentor-mentee pairing, and ethical challenges.